Hubungan Antara Konten Instagram dengan Minat Beli Followers - R. Salwa Dewi Novia Putriawan; Dadan Mulyana (Bandung Conference Series: Communication Management, 2024)
Abstract. The development of technology today is increasingly rapid, one of which is the development of media. The emergence of social media has a considerable influence on society. Social media has a significant role in communicating and has now become a lifestyle among the community as a supporting media for daily activities. Currently, social media is used as an intermediary for its users to exchange information in the form of visual, audio or audio visual. One of them is through Instagram social media which currently in Indonesia has many users, so Instagram social media is often used to convey information that exists by several existing brands, including by one of the local brands Liunic on Things with an Instagram account @liuniconthings. This study aims to determine the relationship between content into the reverie stationery collection on @liuniconthings Instagram account with followers' buying interest. This research uses the theory of uses and effects. The method used is quantitative with a correlational approach. Sampling using simple random sampling. The sample in this study was 94 respondents who based on the results of the calculation of the slovin formula and the sample were followers of Instagram accounts and who liked Instagram account uploads @liuniconthings from July 25, 2023 to August 25, 2023. Data collection techniques are carried out by questionnaires and literature studies. The result of this study is that there is a relationship between Into the Reverie Stationery Collection Content and Follower Buying Interest with a moderate level of relationship, which means that Into the Reverie Stationery Collection content attracts followers buying interest in the medium / not too high category. Abstrak. Perkembangan teknologi saat ini semakin pesat salah satunya perkembangan media. Munculnya media sosial memiliki pengaruh yang cukup besar bagi masyarakat. Media sosial mempunyai peran yang berarti dalam berkomunikasi dan kini sudah menjadi gaya hidup dikalangan masyarakat sebagai media pendukung pada kegiatan sehari-hari. Saat ini media sosial dijadikan perantara untuk para penggunanya agar dapat saling bertukar informasi baik berupa visual, audio ataupun audio visual. Salah satunya melalui media sosial Instagram yang saat ini di Indonesia memiliki banyak pengguna, sehingga media sosial Instagram pun tak jarang dimanfaatkan untuk menyampaikan informasi yang ada oleh beberapa brand yang ada, termasuk oleh salah satu brand lokal Liunic on Things dengan akun Instagram @liuniconthings. Penelitian ini bertujuan untuk mengetahui Hubungan Antara Konten Into the reverie Stationery Collection di Akun Instagram @liuniconthings Dengan Minat Beli Followers. Penelitian ini menggunakan teori uses and effects. Metode yang digunakan adalah kuantitatif dengan pendekatan korelasional. Pengambilan sampel menggunakan simple random sampling. Sampel pada penelitian ini sebanyak 94 responden yang berdasarkan hasil perhitungan rumus slovin dan sampel merupakan pengikut akun Instagram dan yang menyukai unggahan akun Instagram @liuniconthings pada 25 Juli 2023 hingga 25 Agustus 2023. Teknik pengumpulan data dilakukan dengan kuesioner dan studi kepustakaan. Hasil dari penelitian ini adalah terdapat hubungan antara Konten Into the Reverie Stationery Collection dengan Minat Beli Followers dengan tingkat hubungan yang sedang, yang artinya konten Into the Reverie Stationery Collection menarik minat beli followers dengan kategori sedang/tidak terlalu tinggi.